Actividad. (UNED, 2023)
Grupo grande de personas. Aparecen Luis Guillermo Carpio, Patricia González Calderón, Donaval Neil, Vigny Alvarado, Roberto Ocampo Rojas, Carmen Duarte Valerín, Karla Campos Pereira